2020
DOI: 10.3892/mmr.2020.11428
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA NEAT1 promotes ovarian cancer cell invasion and migration by interacting with miR‑1321 and regulating tight junction protein 3 expression

Abstract: Previous studies have reported that long non-coding RNAs (lncRNAs) have a significant role in the metastasis of tumors, including ovarian cancer (OC). The aim of the present study was to demonstrate the function and working mechanism of lncRNA nuclear enriched abundant transcript 1 (NEAT1) in OC. The expressions of NEAT1 in OC were measured by reverse transcription-quantitativePCR (RT-qPCR). The effects of NEAT1 on cell proliferation, invasion, migration and epithelial-mesenchymal transition (EMT) were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…In addition to the promotion of OC cell proliferation, migration, and invasion, NEAT1 was shown to inhibit OC cell apoptosis by upregulating the expression of basic leucine zipper and W2 domain-containing protein 1 (BZW1) via interaction with miR-4500 [84]. NEAT1 also enhanced EMT of OC cells by upregulating the expression of tight junction protein 3 (TJP3) via interaction with miR-1321 [85].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…In addition to the promotion of OC cell proliferation, migration, and invasion, NEAT1 was shown to inhibit OC cell apoptosis by upregulating the expression of basic leucine zipper and W2 domain-containing protein 1 (BZW1) via interaction with miR-4500 [84]. NEAT1 also enhanced EMT of OC cells by upregulating the expression of tight junction protein 3 (TJP3) via interaction with miR-1321 [85].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…As previous validation, NEAT1 is robustly expressed in PCOS tissues and cells, and the ampli cation of NEAT1 facilitates the proliferation and constrains the apoptosis of KGN cells, inducing morbidity of PCOS [6]. Similarly, Luo et al have also elucidated that NEAT1 is enriched in ovarian cancer cell lines, the ovarian cell activities and epithelial-mesenchymal transition are triggered by NEAT1 induction [21].…”
Section: Discussionmentioning
confidence: 84%
“…TJP3 is a member of the membrane-associated guanylate kinase-like (MAGUK) protein family and plays a role in the linkage between the actin cytoskeleton and tight-junctions [38,39]. A study has shown that TJP3 was up-regulated in ovarian cancer and could play an important role in EMT, migratory and invasive potential of ovarian cancer cells [40]. But the role of TJP3 in LSCC is still not understood.…”
Section: Discussionmentioning
confidence: 99%